Laparoscopic-assisted sclerotherapy in pediatric retroperitoneal lymphatic malformations - Shi, Hao; Lv, Zhibao; Xu, Weijue; Liu, Jiangbin; Sheng, Qingfeng; Ren, Xiang; Chen, Zhou (Frontiers in Pediatrics, 2024)
Background：Retroperitoneal Lymphatic malformations (LMs) are rare. Currently, the treatment of retroperitoneal LMs remains challenging.The purpose of this study was to examine safety and efficacy of laparoscopic-assisted sclerotherapy for retroperitoneal LMs in pediatric patients. Methods：We retrospectively reviewed the patients treated with laparoscopic-assisted sclerotherapy for retroperitoneal LMs in a single tertiary medical center between July 2020 and February 2023. Doxycycline was prepared into a solution with a concentration of 10 mg/ml for use in sclerotherapy. Demographic data, clinical features, details of management, and outcomes were collected and analyzed. Results：A total of six patients, comprising three males and three females, were identified. The LMs were categorized into four macrocystic and two mixed-cystic types. The mean age and weight were 52.2 months (range 11-108 months) and 20kg (range 12.5-27.5kg), respectively. Three patients presented with abdominal pain or distension, while the other three patients were asymptomatic. All six patients underwent a total of eight sclerotherapy sessions. Two patients experienced intra-cystic hemorrhage and required a second sclerotherapy session. Only one patient presented with vomiting after sclerotherapy, which resolved spontaneously. Five patients met the complete response criteria, and one patient met the effective criteria. The mean reduction in lesion size was 92.3% (range: 69.9%-99.6%). No further complications or recurrence were recorded during follow-up. Conclusion：Laparoscopic-assisted sclerotherapy is a safe and effective approach for treating retroperitoneal LMs. This technique is applicable for both macrocystic and mixed-cystic retroperitoneal LMs.